Phononic Crystal Sensors: A New Class of Resonant Sensors—Chances and Challenges for the Determination of Liquid Properties - Lucklum, Ralf; Mukhin, Nikolay; Djafari Rouhani, Bahram; Pennec, Yan (Frontiers in Mechanical Engineering, 2021)
Resonant mechanical sensors are often considered as mass balance, which responds to an analyte adsorbed on or absorbed in a thin sensitive (and selective) layer deposited on the surface of the resonant device. In a more general sense, the sensor measures properties at the interface of the mechanical resonator to the medium under inspection. A phononic crystal (PnC) sensor employs mechanical resonance as well; however, the working principle is fundamentally different. The liquid medium under inspection becomes integral part of the PnC sensor. The liquid-filled compartment acts as mechanical resonator. Therefore, the sensor probes the entire liquid volume within this compartment. In both sensors concepts the primary sensor value is a resonance frequency. To become an attractive new sensing concept, specifically as bio and chemical sensor, the PnC sensor must reach an extraordinary sensitivity. We pay attention to the liquid viscosity, which is an important factor limiting sensitivity. The main part of our analyzes has been performed on 1D PnC sensors, since they underlie the same material-related acoustic dissipation mechanisms as 2D and 3D PnC sensors. We show that an optimal relation of frequency shift to bandwidth and amplitude of resonance is the key to an enhanced sensitivity of the sensor to liquid analyte properties. We finally address additional challenges of 2D and 3D PnC sensor design concept. We conclude that the sensor should seek for a frequency resolution close to 10-6 the probing frequency, or a resolution in speed of sound approaching 1 mm.s-1 taking water-based analytes as an example.